The Transformational Leadership of Administrators and Risk Management in School Under Suphanburi Primary Education Service Area Office 3 - Chaobankrang, Chonthira; Tonwimomrat, Sakdipan (Journal of Dhamma for Life, 2024)
The research objectives were to determine: 1) the transformational leadership of school under the Suphanburi Primary Educational Service Area Office 3 2) the risk management of affiliated schools under the Suphanburi Primary Educational Service Area Office 3 and 3) the relationship between the transformational leadership and the risk management under the Suphanburi Primary Educational Service Area Office 3. The sample was 97 schools under the Suphanburi Primary Educational Service Area Office 3. The two respondents from each school consisted of a school director or acting school director and a teacher, with the total of 194. The research instrument was a opinionnaire regarding the leadership based on the concept of Kouzes and Posner and the risk management based on the concept of COSO – ERM 2017. The statistics used for data analysis were frequency, percentage, arithmetic mean, standard deviation, and Pearson’s product–moment correlation coefficient. The research findings were as follows: The transformational leadership of school under the Suphanburi Primary Educational Service Area Office 3 as a whole and as an aspect were at the highest level. The arithmetic mean ranking from the highest to the lowest were as follows; encouraging the heart, modeling the way, enabling others to act, inspiring a shared vision and challenging the process. The risk management of affiliated schools under the Suphanburi Primary Educational Service Area Office 3 as a whole and as an aspect were at the highest level. The arithmetic mean ranking from the highest to the lowest were as follows; governance and culture, information communication and reporting, performance, strategy and objective setting and review and revision. The relationship between the leadership and the risk management of affiliated schools under the Suphanburi Primary Educational Service Area Office 3 were at high correlation in positive way, with significantly level at .01